Marfan syndrome in childhood: parents' perspectives of the impact on daily functioning of children, parents and family; a qualitative study - Jessica Warnink-Kavelaars; Anita Beelen; Sarah Dekker; Frans Nollet; Leonie A. Menke; Raoul H. H. Engelbert (BMC, 2019)
Abstract Background Marfan syndrome (MFS) is a heritable connective tissue disease caused by a defect in FBN1. The diagnosis is based on the revised Ghent criteria. The main features involve the cardiovascular, musculoskeletal, ophthalmic, pulmonary systems and facial features. Although the clinical manifestations of MFS in children are thoroughly addressed in several studies, literature on the impact of MFS on daily functioning is restricted to pediatric advice on sports and leisure participation. Therefore, the full impact of MFS on daily functioning remains unclear. The aim of this qualitative study was to explore parents' perspectives on the impact of MFS on daily functioning of children with MFS aged 4-12 years, themselves and family regarding functional performance, activities, participation, personal and environmental factors, and disease burden. Methods In this qualitative study parents participated in individual semi-structured interviews (n = 10) and 3 focus groups (n = 5, n = 5 and n = 6). Meetings were transcribed, and data were analyzed using thematic analysis. Meaningful concepts were coded, and concepts concerning children with MFS were linked to the International Classification of Functioning, Disability and Health for Children and Youth. Thereafter themes were identified and interpreted. Results Parents reported their children could not keep up with peers because of fatigue, pain and physical impairments. Children experienced participation restrictions in school, sports, play and other leisure activities. Parents reported their child as being different due to physical appearance, which provoked unsupportive attitudes. Parental burden was caused by high care needs, lack of support, a limited social life, and concerns about the child's development. Family burden was caused by adjusted and complex family schedules, other family members with MFS, and reproductive planning decision-making, whereas family cohesiveness and caring were positively perceived factors. Conclusions Parents perceived a large impact of MFS on daily functioning of their children with MFS, themselves and their family. More awareness among all professionals involved in the care of children with MFS and their families is needed so that professionals can address their support needs and provide tailored interventions, rehabilitation and/or educational programs to empower and improve daily functioning of the children, parents and family.